Dinâmica da comunidade microbiana envolvida na fermentação espontânea da puba e caracterização do perfil da qualidade e identidade do produto - Silvia Malta Crispim (2013)
Puba is a Brazilian staple food, obtained by spontaneous submerged fermentation of cassava roots. Data concerning its microbial composition, sanitary characteristics and fermentation dynamic are scarce. This study was conducted to identify the microbial and physico-chemical composition of the product, the sanitary-hygienic parameters associated with the process, and to evaluate some biochemical characteristics of isolated microorganisms with potential use as starter cultures. There were considerable changes in the population of the organisms throughout the fermentation process. Counts showed an increase in number of bacteria and yeasts during the fermentation, and lactic acid bacteria were recovered as the dominant microbiota. The following isolated bacteria were identified as: Bacillus thuringiensis, B. cereus group, B. subtilis group, Lactococcus lactis hordinae, Leuconostoc holzapfelii, Leuconostoc citreum, Lactobacillus acidophilus, L. brevis, L. casei, L. plantarum and L. fermentum. Among isolated yeasts Candida intermedia, C. parapsilosis, C. pararugosa, C. tropicalis, Hanseniaspora guillermondi, Kodamaea ohmeri and Pichia kudriavzevii were identified. The L. plantarum and L. fermentum strains were submitted to molecular typing by rep-PCR and exhibited genetic heterogeneity and species-specific fingerprinting patterns. These strains also showed antagonistic activity against some important foodborn pathogenic bacteria and ability to produce amylase, pectinase, cellulase, lactic acid and hydrogen peroxide. Concluding, during its fermentation process, puba showed a very dynamic and biodiverse microbiota with some components presenting a potential use as starter strains.